Estratégias de reparação na fala gaguejada - Carvalho, Susana de (2014)
Speech production involves a lot of failures that are automatically corrected by speaker, suggesting the existence of an internal self-monitoring system. Often considered as linguistic processing errors, such failures may reveal difficulties in neuromotor or perceptual processing. The aim of this study was to analyze the self-monitoring of speech of adults who stutter, comparing it to fluente adults. It is an observational and analytical study, which was attended by 70 participants, adults, males, native speakers of Brazilian Portuguese, with high school degree. The participants were allocated into two groups: 35 fluent adults and 35 adults who stutter. All the volunteers were asked to carry out an oral reading task of a text in Brazilian Portuguese. The task was recorded and literally transcribed. The examination of samples of speech enabled the identification of errors and their classification. The errors were categorized as ignored, corrected covert and corrected explicit. The data were submitted to descriptive and analytical statistics. No difference was observed between the number of errors ignored by adults who stutter or fluent adults. There are differences between the groups with regard to corrections for both covert and explicit errors. It is concluded that fluent adults and adults who stutter show the same skills of self-monitoring of speech. Repair strategies, in disfluent speech, differ in some aspects of the strategies of fluent speakers.